GREEN INNOVATIONS AND THEIR APPLICATION IN MODERN BUSINESS - Sara Drakul (Collection of Papers New Economy, 2025)
Rapid industrial and technological development has significantly impacted the natural environment. As a result, environmental protection has become an imperative. In response to growing ecological awareness and regulatory pressure, companies are adopting innovative practices across their operations. Green innovations now play a key role in reducing the environmental footprint of business activities. Green innovation involves implementing eco-friendly products and processes, improving resource efficiency, and minimizing environmental harm. These innovations often require new or improved business methods, technologies, and materials aimed at maximizing positive impact. In practice, this includes new production equipment, sustainable raw materials, and cleaner manufacturing techniques. Renewable energy is gaining ground, driven by innovations that lower costs and increase efficiency. As renewables begin to replace fossil fuels, they offer lower carbon emissions and reduced pollution, which are essential for addressing the climate crisis. Green innovation is therefore crucial for managing renewable energy sources and achieving sustainable business models. Industries with high environmental impact are more likely to adopt green innovations. The automotive industry, one of the major polluters both during production and through its products, has introduced green technologies to reduce its footprint. Companies like General Motors and Tesla are leading examples of this transformation, demonstrating how green innovation supports long-term environmental and economic sustainability.